pegegog 2023
DOI: 10.47750/pegegog.13.02.37
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Psychological Capital Between Academic Stress and Well-Being Among University Students

Abstract: In the current study, we investigated the relationships among academic stress, psychological capital (PsyCap), and well-being and the effect of the demographic variables of gender, majors, and academic years on academic stress and PsyCap. We used the structural equation model to investigate the mediating role of PsyCap between academic stress and well-being. The participants (N = 827) included students from a midsized university in the Eastern Province of Saudi Arabia (636 females, 191 males) who comprised 450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…It has been mentioned that PsyCap has a significant relationship with MH [ 35 , 43 ]. PsyCap, as a buffering factor against student stress, indicates that it reduces the association between stress and adverse consequences among students [ 44 ]. A study [ 45 ] discovered connections between PsyCap and the MH status of students, suggesting that higher levels of PsyCap were positively connected with improved MH.…”
Section: Introductionmentioning
confidence: 99%
“…It has been mentioned that PsyCap has a significant relationship with MH [ 35 , 43 ]. PsyCap, as a buffering factor against student stress, indicates that it reduces the association between stress and adverse consequences among students [ 44 ]. A study [ 45 ] discovered connections between PsyCap and the MH status of students, suggesting that higher levels of PsyCap were positively connected with improved MH.…”
Section: Introductionmentioning
confidence: 99%
“…In the academic context, general and specific indices of student well-being can play a key role in counteracting the negative effects of stress, acting as protective factors both for the development of stress (general and academic) and for the coping/adaptation to stress itself [ 16 , 17 , 18 , 19 , 20 ]. Indeed, despite the presence of possible risk factors for the development of stress in the academic environment, not all students experience its potential negative impact.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, a study involved with 827 university students also found that psychological capital was a mediator between stress and well-being. In other words, the student's stress level can be reduced by enhancing the student's psychological capital level, subsequently contributing to a positive effect on the student's well-being [8].…”
Section: Introductionmentioning
confidence: 99%